2005
DOI: 10.1017/s0024282905014982
|View full text |Cite
|
Sign up to set email alerts
|

Isidia ontogeny and its effect on the CO2 gas exchanges of the epiphytic lichen Pseudevernia furfuracea (L.) Zopf

Abstract: The development of isidia in thalli of Pseudevernia furfuracea from the Carnic Alps (North-eastern Italy), and the effects of these structures on CO 2 gas exchanges were investigated. The ontogenetic events were studied by comparison of sections stained with different histochemical tests and SEM observations. A high cell turnover rate in both symbiotic partners is the first sign of isidium development, followed by an increased aplanosporogenesis of algae and growth of neighbouring medullary hyphae which become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…The upper cortex organization in both species also seems to be associated with thallus water uptake and CO 2 diffusion capacity, as pointed out by several authors (Hale 1981;Elix 1993;Tretiach et al 2005;Crespo et al 2006;Barbosa et al 2009b). High cortex thickness may work as a barrier to water diffusion, lengthening thallus saturation time, as observed by Hale (1981) in other Parmeliaceae species.…”
Section: Discussionmentioning
confidence: 53%
“…The upper cortex organization in both species also seems to be associated with thallus water uptake and CO 2 diffusion capacity, as pointed out by several authors (Hale 1981;Elix 1993;Tretiach et al 2005;Crespo et al 2006;Barbosa et al 2009b). High cortex thickness may work as a barrier to water diffusion, lengthening thallus saturation time, as observed by Hale (1981) in other Parmeliaceae species.…”
Section: Discussionmentioning
confidence: 53%
“…CO 2 gas exchange was measured with an Infrared Gas Analyzer (IRGA) LICOR-6250, operating in a closed system (for technical details, see Tretiach et al 2005). Nearly natural spectrum light was provided by a FL-400 Lighting Unit (Walz), powered by an Osram HLX 250 W lamp.…”
Section: Co 2 Gas Exchangementioning
confidence: 99%
“…However, as pointed by Hale (1983), the major question in using these characteristics is the lack of studies and understanding of their origin and ontogeny. The most recent studies on isidia have focused on their dispersion pattern, settling and survival (Gilbert, 1988;Scheidegger et al, 1995;Zoller et al, 2000), but their anatomical structure and ontogenesis are scarcely reported (Tretiach et al, 2005).…”
Section: Introductionmentioning
confidence: 99%